Incidence and outcomes of cardiac tamponade in patients undergoing cardiac resynchronization therapy. (1st December 2018) - Adegbala, Oluwole; Olagoke, Olakanmi; Adejumo, Adeyinka; Akintoye, Emmanuel; Oluwole, Adegbola; Alebna, Prince; Williams, Karlene; Lieberman, Randy; Afonso, Luis
Abstract: Introduction: Cardiac tamponade is a severe complication of cardiac resynchronization therapy (CRT) implantations. We provide a contemporary large-scale study evaluating the incident trends, predictors and impact of cardiac tamponade in patients undergoing CRT. Method: Data were obtained from the Nationwide Inpatient Sample (NIS) of 2007 through 2014. Trends in the annual rates of tamponades in CRT implantation were assessed using negative binomial regressions. Hierarchical mixed-effects logistic regression models were built to determine the independent predictors of tamponade in CRT implantation and 1:1 propensity-matched analysis performed to examine the impact of tamponade on outcomes. Result: An estimated 310, 704 CRT implantations were performed in the United States between 2007 and 2014, out of which 536 patients (0.17%) developed procedure-related cardiac tamponade. A significant increasing trend in the tamponade incidence was observed over the 8-year study period [1.65 per 10, 000 CRT implantation in 2007 to 38.16 in 2014 (p < 0.001)]. After multivariable adjustment, female sex and coagulation disorder were found to be independently associated with higher odds of tamponade. Conversely, prior history of CABG procedure was associated with lower odds of tamponade. CRT complicated with tamponade had significantly increased in-hospital mortality, bleeding requiring transfusion, prolonged hospital stay and increased cost. Conclusion: We found an increasing trend in the incidence of post CRT tamponade among hospitalized patients between 2007 and 2014. Female gender and coagulation disorder were associated with the development of tamponade among recipients of CRT. Risk stratification of patients who are undergoing CRT is crucial to improving outcome in CRT implantation. Highlights: The incidence of cardiac tamponade post CRT placement is on the rise. Cardiac tamponade is more common among women and those with coagulation disorder. Prior CABG is associated with reduced cardiac tamponade in recipients of CRT. Post-CRT cardiac tamponade is associated with worse in-hospital outcomes.